Research models and methods in legal translation - Biel, Lucja; Engberg, Jan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
The introduction presents an overview of traditional research methods in Legal Translation Studies and discusses new developments as represented by the papers comprised in the special issue. The predominant methodology is corpus-based; there is a clear shift from qualitative to quantitative methods. Corpus-based methods are applied to the study of local phenomena, such as terms or phrasemes, and of global phenomena, such as genres and macrogenres, as well as they analyse practical decisions made by legal translators with a view to developing new tools and resources for translators. Other directions include: the application of comparative law methods, sociology of translation and Critical Discourse Analysis. Overall, there is growing interest in the communicative, pragmatic, cognitive and social aspects of legal translation. As the papers demonstrate, research into legal translation requires methodological eclectism and triangulation, as well as further integration along the interdisciplinary lines.